Philosophy in Engineering Systems of Action: Analysis and Interpretation of the Selected Ontological Aspects of Józef Konieczny’s Theory of Action - Smolnik Maksymilian (Studies in Logic, Grammar and Rhetoric)
Designing and examining systems of action plays an important role in modern engineering. Such a general approach to actions is also supportive to the discussions on the development of artificial intelligence agents. As a philosophically remarkable and practically useful approach to actions the theory of action proposed by the Polish philosopher, scientist and military specialist Józef Konieczny undergoes here further considerations.